The expected impact of COVID-19 on the housing market - Charmaine Fritsche (FOM Hochschule für Oekonomie & Management, KCV KompetenzCentrum für angewandte Volkswirtschaftslehre, 2021)
The outbreak of COVID-19 has been an unprecedented disruptor in the world's social and economic fabric. However, the crisis has only barely affected the real estate market, which continues its upward trend in many countries as of the fourth quarter of 2020. Drivers of housing prices and possible effects of the pandemic on the housing market are examined in this article. Special emphasis lies on developments in the EU.
Keywords: 330; housing prices; real estate; remote work; COVID-19